Physiological and Transcriptomic Analysis of Oat Seedlings in Response to Drought Stress - Walter, Biljana; Bhusal, Dimo; Byeon, Chanoh (Journal of Functional Materials and Applied Engineering, 2022)
This study used oat (Avena sativa) as material to systematically analyze physiological responses and transcriptomic changes under simulated drought stress. Physiological results showed that drought stress significantly reduced leaf relative water content (RWC) and increased relative electrical conductivity (REC), while inducing dynamic changes in antioxidant enzyme activities (superoxide dismutase [SOD], peroxidase [POD], and catalase [CAT]). Transcriptome sequencing (RNA-Seq) revealed extensive gene expression changes, with 369 common differentially expressed genes (DEGs)​ across all stress time points—these were enriched in plant hormone signal transduction, mitogen-activated protein kinase (MAPK) signaling pathway, and starch/sucrose metabolism. Weighted gene co-expression network analysis (WGCNA) further identified one core module positively correlated with phenotypic traits, from which 9 hub genes​ were screened. These genes are involved in cell wall reinforcement, osmotic protection, and metabolic regulation—playing core roles in oat’s drought response. This study provides a theoretical basis for understanding the molecular mechanisms of oat drought resistance.